Packaging Design as a Media for Developing the Potential of Small and Medium Micro Enterprises (MSMEs) in the Culinary Sector Typical of the Region in the Creative Industry - R A Dewi; R Wahdiniwaty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This design aims to design a typical regional food packaging design, namely Kalua Jeruk which is attractive and follows food labeling rules to develop the potential of Small, and Medium Micro Enterprises (MSMEs), especially in the culinary field. This design uses qualitative research. The data source used in the study was an interview with one of MSME Kalua Jeruk entrepreneurs and respondents related to good packaging design for regional specialties. In addition, observations are used to observe the making process of Kalua Jeruk. The steps taken in this design are to observe the process of making Kalua Jeruk, analyze the results of interviews, and design a good packaging for it. Based on the analysis data, it was concluded that need to package designs are attractive, informative, and follow food labeling rules to improve the product image and consumer purchasing power. Moreover, Kalua Jeruk has a uniqueness that is made from processed Pomelo peel with hereditary recipes. The result of this design is in the form of a 3-Dimensional Kalua Jeruk packaging design mockup which is expected to be a reference for packaging design, especially for developing the potential of MSMEs in the culinary field in the creative industries.